Experience the Past in the Present with Immersive Technologies - Chang, Tin Lan; Martins de Abreu, F. (Instituto Politécnico de Portalegre, 2022)
Countless historical sites worldwide have become unrecognisable based on their historical context. Many are cultural heritage structures with significant historical and aesthetic importance. The majority have not been well preserved; worse, some were demolished (Stenning, 2015). Furthermore, structures are part of a dynamic and changing environment, and their location within the original landscape is not always clear. People have gradually forgotten cultural traditions as environments where historical stories took place, and the look and feel have been corrupted. Immersive Virtual Reality (V.R.) allows us to relive and explore the past. However, in the Pearl River Delta Region, specifically Macau S.A.R., V.R. is still in its infancy and is not frequently used for reproducing historical sceneries. Our research focuses on reproducing heritage structures and scenery based on scarce historical information. It shows how to incorporate facts and memories into the design and create engaging, immersive experiences in V.R. scenery that takes place, both inside and outside of a cultural heritage site that has lost its original appearance. Following this, a prototype was created with specific parameters relating to past and present sceneries. We partially reproduced an existing building complex currently being used for creative and commercial purposes, but it was a shelter for the poor and a house for old ladies to live in. There were not enough facts or images linked to the inner space in the past. Inadequate information allows audiovisual scene creators to be more imaginative. The prototype focuses on a functional design that integrates cultural traits tied to local industries. The researcher used image processing software, and web 3D tools (A-Frame 1.1.0). Users can navigate by virtually “walking” and starting the visual tour; simultaneously, the story unfolds as the timeline progresses. After entering, the users jump from the present to a specific era in the past. With audio guidance, users enter the private space, shared areas, working space, etc. Users can interact with objects from the virtual scenes while the interface displays relevant audiovisual introductions. Users could utilise the virtual system to learn how the old ladies led their daily lives in the Pearl River Delta Region and grasp the local single ladies’ group lifestyle at a specific time in the past (Kwong, 2020). The interactive experience enhances the users’ interest; additionally, the users become more familiar with the region’s traditional customs. With this approach, we can create old stories using modern technology. A-Frame provides users with great convenience and can be used by any Internet browser without relying on professional V.R. devices. The content from this usage provides a greater understanding of our heritage buildings and their historical context to the wider community. This could be used in other heritage sites worldwide to reproduce and maintain structural qualities over time. This immersive experience could be a means to navigate the past while in the present. This application could benefit exhibition developers, and visitors, notably in exhibition guided tours, virtual tours inside museums, or educational assisted historical storytelling.

An Integrated Learning Platform Focusing on STEAM and Collaborative Modules for Macau - Cheng, Un Man; Martins de Abreu, F. (International Journal of Creative Interfaces and Computer Graphics (IJCICG), 2022)
In Macau, the effectiveness of traditional classroom learning is questioned as the problem is discovered by the changes in technology advances, social media, and the varieties of learning methods. Learning experiences, interests, discoveries, and creativity development are considered essential to ac...
Publisher: IGI Global

Audience Participation in Interactive Art Systems: Is Instructional Signage a Necessary Evil? - Cordeiro, João; Martins de Abreu, F.; Estadieu, Gerald (Proceedings of the 8th International Conference on Digital Arts, 2017)
2 citations (Crossref) [2022-10-27]

Book of Proceedings of ARTeFACTo 2022 Macao, Third International Conference on Digital Creation in Arts, Media and Technology - Emerging Extended Realities - Estadieu, G; Martins de Abreu, F.; Caires, Carlos; Fernandes Marco, A. (IEEE, 2023)

3D Printing Objects As Installation Art: Standing Humanity: 3D Yan Character - Estadieu, Gérald; Martins de Abreu, F.; Barbosa, Álvaro (Proceedings of the 8th International Conference on Digital Arts (ARTECH 217), 2017)
0 citations (Crossref) [2022-09-21] GSCC: 0000000

Beyond Physical Boundaries—Organising a Virtual Exhibiton with NFTs for an International Conference - Estadieu, Gerald; Ng, S.O.K.M.; Martins de Abreu, F.; Farinha, D.F. (11th International Conference on Digital and Interactive Arts (ARTECH 2023), 2023)

Re-experiencing Street Signage with Augmented Reality around the City of Macau - Lio, Si Weng; Martins de Abreu, F. (Proceedings of the 11th International Conference on Digital and Interactive Arts (ARTECH2023), 2023)

Creative Engagement: Multimodal digital games in children's learning environment in Macau S.A.R. - Martins de Abreu, F.; Barbosa, Álvaro (Proceedings of the 8th International Conference on Digital Arts, 2017)
One of the biggest challenges that we have encountered, when trying to encourage digital games in schools, is trying to explain what its benefits are in teaching and learning environments. In this pilot experimental study we explore how multimodal audio and visual games can be used in learning environments for children, specifically by fostering creative behaviors through User-Centered design approaches. To achieve this objective, a framework is being developed with multimodal experiences based on flexible design patterns that exploits basic visual and audio elements, allowing children from three to six years of age to play and learn through fun and subsequently trigger creative behaviors. These studies are making use of tangible objects, digital games and mobile platforms. We are making use of commercial digital games to understand and discuss the affordances of these games in an educational environment and how they support creativity in learning. (Fig.1)
Keywords: Children; Creative Learning; Devices; Digital Games; Mobile; Multimodal; Tangible Technologies; User-Centered Design

Cyberculture and Multimodal Digital Games in Learning Environments: Fostering Creativity in Macau’s Educational System - Martins de Abreu, F.; Barbosa, Alvaro (2018)

The impact of multimodal digital games in children’s learning environments - Martins de Abreu, F.; Barbosa, Alvaro (2017)

Multimodal Game Design Framework for Creativity in Macau's Educational System Through Digital and Tangible Games: Chinese, Portuguese, and English Languages - Martins de Abreu, F.; Barbosa, Álvaro Mendes (International Journal of Creative Interfaces and Computer Graphics (IJCICG), 2022)
Creativity and collaboration are crucial to learning development in today's fast-paced educational environment. New technology can bridge humans and their natural needs through immersion in digital environments with physical objects. As knowledge and information evolve, digital interactive experienc...
Publisher: IGI Global